Relationship between Social Media Dependence and Social Connectedness among adolescents - Supreet , Kaur; Yashpreet, Kaur (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the current study was to investigate the relationship between Social Media Dependence and Social Connectedness among adolescents . Sample comprised of of 200 adolescents studying in VIII class were selected by using random sampling technique. Mixed method two phase design of study was employed. Two research instruments were used. For quantitative data “Adapted Internet Addiction Test” and for qualitative part semi-structured interview schedule were employed. From phase I it was concluded that 2.5% of adolescents are experiencing significant problems in their life because of their excessive usage of social media. From phase II it became clear that social media dependence fosters the sense of belongingness but excessive social media usage creates problems in the social connectedness in the real world context.